Flame-retardant modified hypophosphite and preparation method thereof
By forming a double-layer clad structure of phosphite and cyanurate on the surface of the hypophosphite, the problem of low thermal decomposition temperature of the existing hypophosphite flame retardant is solved, and a flame-retardant modified hypophosphite with high thermal decomposition temperature and high safety is achieved.
Patent Information
- Application Number
- CN202411988019.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The thermal decomposition temperature of existing hypophosphite flame retardants is not high, easily ignited, has poor safety, and is a flammable solid.
The flame-refractory modified hypophosphate is adopted with a double-layer coated structure. The inner core is hypophosphate, the inner layer is phosphite, and the outer layer is cyanurate. The supramolecular network structure is formed to improve thermal stability by forming a phosphite layer on the hypophosphite surface and forming a cyanurate layer thereon.
The thermal decomposition temperature of hypophosphite is significantly increased, and the thermal decomposition temperature of 1 wt% is ≥350℃. It is not a flammable solid and has high safety. It meets the measurement method in GB 19521.1 "Safety Specifications for the Inspection of Hazardous Characteristics of Flammable Solids Hazardous Cargoes".
Smart Images

Figure CN119708636A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flame retardant preparation and application, and relates to a flame retardant modified hypophosphite and a preparation method thereof. Background Art
[0002] As an emerging flame retardant, hypophosphites have attracted widespread attention due to their high phosphorus content, low impact on polymer decomposition during processing, and non-interference with the performance of plastic molding compositions. Among them, aluminum hypophosphite is particularly noteworthy for its slightly soluble in water, non-volatility in the preparation and processing of thermoplastic polymers, and excellent mechanical properties and weather resistance during processing. According to the UL94 standard, polymer compositions containing aluminum hypophosphite can achieve a V0 flame retardant level at a thickness of 0.7mm. At the same time, under the IEC61335-1 standard, products with a thickness of 0.8mm have also successfully passed the GWIT test, showing excellent flame retardant properties.
[0003] However, hypophosphite flame retardants also have significant disadvantages. According to the industry standard HG / T 4833-2015 for industrial aluminum hypophosphite and the classification of GB12268-2012, aluminum hypophosphite is classified as a flammable solid. Although its 1wt% thermal decomposition temperature is not less than 280°C, this thermal stability still needs to be improved. The flammability of aluminum hypophosphite stems from its poor thermal stability. When heated, it is easy to generate phosphine gas, which is ignited and continues to burn.
[0004] To solve this problem, researchers have made many attempts. For example, in the literature (Preparation of Highly Stable Microencapsulated Aluminum Hypophosphite and Its Application in Flame-Retardant PA6 [J]. Engineering Plastics Application, 2019, 47(09): 139-143.), an MCA-coated microencapsulated aluminum hypophosphite was prepared, which improved the thermal stability of aluminum hypophosphite to a certain extent, but failed to change its flammable solid properties.
[0005] Patent application CN105457574A discloses a melamine resin-coated aluminum hypophosphite. Although the modified aluminum hypophosphite prepared by this method can achieve self-extinguishing when away from fire, thus improving transportation safety, it still falls within the category of flammable solids.
[0006] Therefore, there is a need for a flame retardant modified hypophosphite and a preparation method thereof that can solve the above problems. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art, to provide a flame retardant modified hypophosphite and a preparation method thereof, to overcome the defects of the hypophosphite flame retardant in the prior art, such as low thermal decomposition temperature, easy ignition, poor safety, and being a flammable solid dangerous goods as determined by the method in GB19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A flame-retardant modified hypophosphite has a double-layer coating structure, wherein the inner core is hypophosphite, the inner layer is phosphite, and the outer layer is cyanurate.
[0010] As the preferred technical solution:
[0011] The flame retardant modified hypophosphite as described above has a core diameter of 1 to 50 μm, an inner layer thickness of 10 to 150 μm, and an outer layer thickness of 10 to 50 μm.
[0012] The flame retardant modified hypophosphite as described above, wherein the hypophosphite is one or more of aluminum hypophosphite, calcium hypophosphite, magnesium hypophosphite, zinc hypophosphite, tin hypophosphite, stannous hypophosphite, cerium hypophosphite and barium hypophosphite.
[0013] A flame retardant modified hypophosphite as described above, wherein the phosphite is one or more of calcium phosphite, aluminum phosphite, magnesium phosphite, zinc phosphite, tin phosphite, stannous phosphite, iron phosphite, lanthanum phosphite and barium phosphite.
[0014] In the flame-retardant modified hypophosphite as described above, the cyanurate is one or more of melamine cyanurate, dicyandiamide cyanurate, meleamine cyanurate, melem cyanurate and cyanuric acid-based graphite carbon nitride.
[0015] The flame retardant modified hypophosphite as described above has a high thermal decomposition temperature, 1wt% thermal decomposition temperature ≥ 350°C, high safety, and is not a flammable solid as determined by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0016] The present invention also provides a method for preparing a flame retardant modified hypophosphite as described in any one of the above items, comprising the following steps:
[0017] 1) Add hypophosphite and soluble metal salt into water, heat to 80-100°C, and stir for 15-30 minutes; during this process, hypophosphite absorbs soluble metal salt positive ions through its own high surface binding energy;
[0018] 2) adding alkaline substance I to the system of step 1), keeping the temperature for reaction for 0.5 to 4 hours, and then adding phosphorous acid to continue the reaction for 0.5 to 4 hours; during this process, alkaline substance I reacts with soluble metal salt positive ions to generate metal hydroxide on the surface of hypophosphite, and then the metal hydroxide continues to react with phosphorous acid to form a tightly packed phosphite layer, and the phosphite layer has a porous structure;
[0019] 3) adding alkaline substance II to the system of step 2), stirring for 15 to 30 minutes, adding cyanuric acid and keeping warm for 0.5 to 4 hours, and obtaining flame-retardant modified hypophosphite through post-treatment (natural cooling, filtering, drying, and crushing); in this process, alkaline substance II is adsorbed in the porous structure of the hypophosphite layer, and then undergoes hydrogen bond self-assembly reaction with the added cyanuric acid to form a supramolecular network structure, i.e., the outer cyanurate layer.
[0020] As the preferred technical solution:
[0021] In the method as described above, m(hypophosphite):m(soluble metal salt+alkaline substance I+phosphorous acid):m(alkaline substance II+cyanuric acid):m(water)=100:10~200:10~200:500~1000, m(hypophosphite) represents the mass of hypophosphite, m(soluble metal salt+alkaline substance I+phosphorous acid) represents the total mass of soluble metal salt, alkaline substance I and phosphorous acid, m(alkaline substance II+cyanuric acid) represents the total mass of alkaline substance II and cyanuric acid, and m(water) represents the mass of water; the molar ratio of soluble metal salt, alkaline substance I and phosphorous acid is 1:1~6:1~3; the molar ratio of alkaline substance II and cyanuric acid is 1:0.8~1.5.
[0022] In the method as described above, the soluble metal salt is one or more of soluble calcium salt, aluminum salt, magnesium salt, zinc salt, tin salt, stannous salt, iron salt, ferrous salt, lanthanum salt and barium salt; the alkaline substance I is one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, strontium hydroxide, barium hydroxide, mercuric hydroxide, diammine silver hydroxide, calcium hydroxide and ammonia water; the alkaline substance II is one or more of melamine, dicyandiamide, melamine, melamine and graphite-like carbon nitride.
[0023] Principle of the invention:
[0024] After the flame-retardant modified hypophosphite of the present invention is heated, the outer coating layer (cyanurate) decomposes after heating to produce nitrogen-containing inert gas, absorbs combustion heat, and prevents the internal temperature of the product from rising further. When the temperature exceeds the action limit of cyanurate, the inner coating layer (phosphite) removes crystal water, and further generates a dense metal oxide heat insulation layer under the action of oxygen, which plays a heat-absorbing and insulating role. Through the joint action of these two coatings, the temperature of the inner hypophosphite does not exceed its decomposition temperature during the entire test process, thereby avoiding the generation of flammable phosphine gas, and then meets the determination method in GB 19521.1 "Safety Specification for Inspection of Dangerous Characteristics of Flammable Solid Dangerous Goods", and does not belong to flammable solids. In addition, due to the presence of the tightly wrapped phosphite layer, the thermal decomposition temperature of the inner hypophosphite is also improved, and the improvement of heat resistance further enhances the application safety of the product of the present invention.
[0025] There is a difficulty in the preparation process of flame-retardant modified hypophosphite: phosphite is difficult to coat on hypophosphite. If metal hydroxide is directly used to mix with hypophosphite and then react with phosphorous acid, a mixed structure of hypophosphite and phosphite will be formed, rather than a coating structure. The present invention firstly adsorbs soluble metal salt positive ions to the surface of hypophosphorous acid through the high surface binding energy of hypophosphite itself, and then adds alkaline substance I, which can ensure that the metal hydroxide generated by the reaction spontaneously grows tightly on the surface of hypophosphite, and then reacts with phosphorous acid to further form a tightly wrapped phosphite layer.
[0026] Beneficial effects:
[0027] (1) The present invention forms two coating layers on the surface of hypophosphite so that the temperature of the inner core hypophosphite does not exceed its decomposition temperature during the entire test process, thereby avoiding the generation of flammable phosphine gas, thereby meeting the determination method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods" and does not belong to flammable solids.
[0028] (2) The present invention can tightly wrap the hypophosphite through the phosphite layer, so that the thermal decomposition temperature of the inner core hypophosphite is also increased. The improvement of heat resistance further enhances the application safety of the product of the present invention.
[0029] (3) The preparation process of the present invention is reasonable, the product yield is high, the raw material sources are wide, and it is easy to industrialize production. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an infrared spectrum of the flame retardant modified hypophosphite prepared in Example 1 of the present invention;
[0031] Figure 2 This is an electron microscope image of the flame retardant modified hypophosphite prepared in Example 1 of the present invention;
[0032] Figure 3 This is an electron microscope image of unmodified aluminum hypophosphite. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0034] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.
[0035] The graphite-like carbon nitride used in the following examples was prepared in the literature (Preparation of graphite-like carbon nitride and its synergistic system and study of flame-retardant polyamide 6 [D]. Donghua University, 2023. DOI: 10.27012 / d.cnki.gdhuu.2023.000031.).
[0036] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0037] 1wt% thermal decomposition temperature: 10-15 mg of the flame-retardant modified hypophosphite prepared in each embodiment and each comparative example was taken as a sample, and then the sample was tested by a thermogravimetric analyzer (manufacturer: NETZSCH, Germany, model: TG209F1) using a thermogravimetric method; wherein the test conditions were: nitrogen atmosphere, heating rate: 10°C / min.
[0038] Example 1
[0039] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0040] 1) Add aluminum hypophosphite and aluminum sulfate into water, heat to 80°C, and stir for 15 minutes;
[0041] 2) adding sodium hydroxide to the system of step 1), keeping the temperature for reaction for 0.5 h, and then adding phosphorous acid to continue the reaction for 4 h;
[0042] 3) adding melamine to the system of step 2), stirring for 15 minutes, adding cyanuric acid and keeping the temperature for 4 hours, and obtaining flame-retardant modified hypophosphite after post-treatment;
[0043] In steps 1) to 3), m(aluminum hypophosphite):m(aluminum sulfate+sodium hydroxide+phosphorous acid):m(melamine+cyanuric acid):m(water)=100:10:10:500, m(aluminum hypophosphite) represents the mass of aluminum hypophosphite, m(aluminum sulfate+sodium hydroxide+phosphorous acid) represents the total mass of aluminum sulfate, sodium hydroxide and phosphorous acid, m(melamine+cyanuric acid) represents the total mass of melamine and cyanuric acid, and m(water) represents the mass of water; the molar ratio of aluminum sulfate, sodium hydroxide and phosphorous acid is 1:1:1; the molar ratio of melamine and cyanuric acid is 1:1.
[0044] The flame retardant modified hypophosphite (its infrared spectrum is as follows Figure 1 As shown in the electron microscope image Figure 2 As shown in the figure, the outer particles of the flame-retardant modified hypophosphite present a tightly packed structure. The electron microscope image of the unmodified aluminum hypophosphite is shown in Figure 3As shown, the aluminum hypophosphite is dispersed) with a double-layer coating structure, the inner core is aluminum hypophosphite, the inner layer is aluminum phosphite, and the outer layer is melamine cyanurate; the diameter of the inner core is 1μm, the thickness of the inner layer is 10μm, and the thickness of the outer layer is 50μm; the thermal decomposition temperature of 1wt% of the flame-retardant modified hypophosphite is 350℃, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0045] Comparative Example 1
[0046] A method for preparing a modified hypophosphite is basically the same as that in Example 1, except that step 3) is not performed.
[0047] The 1wt% thermal decomposition temperature of the modified hypophosphite finally obtained is 320°C, and it is a flammable solid as determined by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0048] By comparing Comparative Example 1 with Example 1, it can be seen that the 1wt% thermal decomposition temperature of the modified hypophosphite prepared in this comparative example is reduced, and it is determined to be a flammable solid by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods". This is because the modified hypophosphite prepared in this comparative example has no outer coating layer, that is, it does not contain melamine cyanurate, and it cannot decompose to absorb heat and produce gases such as ammonia and water vapor when ignited, and cannot form a non-combustible micro-combustion environment, which causes the flame heat to be directly concentrated on the inner layer and the inner core, and because the dehydration speed of the inner aluminum phosphite layer is too fast, it cannot quickly form a dense metal oxide insulation layer with oxygen, resulting in a rapid increase in the temperature of the inner core, generating phosphine gas, and then causing the aluminum phosphite in the inner core to be ignited, and after ignition, it cannot self-extinguish and will quickly spread the flame, so that the 1wt% thermal decomposition temperature of the modified hypophosphite prepared in this comparative example is reduced and it is a flammable solid.
[0049] Comparative Example 2
[0050] A method for preparing a modified hypophosphite is basically the same as that of Example 1, except that step 2) is not performed and step 3) is to add materials to the system of step 1).
[0051] The structure of the modified hypophosphite finally obtained is basically the same as that of Example 1, except that: there is only one coating layer composed of melamine cyanurate outside the inner core; the 1wt% thermal decomposition temperature of the modified hypophosphite is 300°C, and it is determined to be a flammable solid by the method in GB19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0052] Comparing Comparative Example 2 with Example 1, it can be seen that the 1wt% thermal decomposition temperature of the modified hypophosphite prepared in this comparative example is lowered, and it is a flammable solid as determined by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods". This is because although the outer layer of melamine cyanurate has the function of absorbing heat and producing ammonia, water vapor and other gases after thermal decomposition, as the heating continues, due to the absence of the inner layer of aluminum hypophosphite, a dense metal oxide thermal insulation layer cannot be formed, so the heat of the inner core will eventually exceed its decomposition temperature, generating phosphine gas, and the inner core aluminum hypophosphite is ignited, which is a flammable solid.
[0053] Comparative Example 3
[0054] A method for preparing a modified hypophosphite is basically the same as that in Example 1, except that:
[0055] 1) Add sodium hydroxide and aluminum sulfate into water, heat to 80°C, and keep the temperature to react for 0.5h;
[0056] 2) Add aluminum hypophosphite to the system of step 1) and stir for 15 minutes, then add phosphorous acid and continue the reaction for 4 hours.
[0057] The modified hypophosphite finally obtained has a coating structure, with a mixed form of aluminum hypophosphite and aluminum phosphite inside and melamine cyanurate as the outer layer; the 1wt% thermal decomposition temperature of the modified hypophosphite is 310°C, and it is a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0058] By comparing Comparative Example 3 with Example 1, it can be seen that the 1wt% thermal decomposition temperature of the modified hypophosphite obtained in this comparative example is reduced, and it is determined to be a flammable solid by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods". This is because the reactions in steps 1) and 2) of this comparative example are essentially to directly mix the metal hydroxide with the hypophosphite, and then react with phosphorous acid, which will result in the formation of a mixed structure of hypophosphite and phosphite rather than a coating structure, and then when subjected to flame, a dense metal oxide insulation layer cannot be formed, resulting in the temperature of the hypophosphite being too high, generating phosphine gas, and causing the hypophosphite to be ignited, thereby resulting in the 1wt% thermal decomposition temperature of the modified hypophosphite obtained in this comparative example being reduced and being a flammable solid.
[0059] Example 2
[0060] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0061] 1) Add calcium hypophosphite and calcium chloride into water, heat to 90°C, and stir for 30 minutes;
[0062] 2) adding potassium hydroxide to the system of step 1), keeping the temperature for reaction for 2.5 hours, and then adding phosphorous acid to continue the reaction for 2.5 hours;
[0063] 3) adding dicyandiamide to the system of step 2), stirring for 23 minutes, adding cyanuric acid and keeping the temperature for reaction for 2.5 hours, and obtaining flame-retardant modified hypophosphite after post-treatment;
[0064] In steps 1) to 3), m(calcium hypophosphite):m(calcium chloride+potassium hydroxide+phosphorous acid):m(dicyandiamide+cyanuric acid):m(water)=100:200:200:1000, m(calcium hypophosphite) represents the mass of calcium hypophosphite, m(calcium chloride+potassium hydroxide+phosphorous acid) represents the total mass of calcium chloride, potassium hydroxide and phosphorous acid, m(dicyandiamide+cyanuric acid) represents the total mass of dicyandiamide and cyanuric acid, and m(water) represents the mass of water; the molar ratio of calcium chloride, potassium hydroxide and phosphorous acid is 1:6:1; the molar ratio of dicyandiamide and cyanuric acid is 1:1.5.
[0065] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of calcium hypophosphite, an inner layer of calcium phosphite, and an outer layer of dicyanuric acid dicyandiamide; the diameter of the inner core is 5 μm, the thickness of the inner layer is 105 μm, and the thickness of the outer layer is 15 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 375°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0066] Example 3
[0067] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0068] 1) Add magnesium hypophosphite and magnesium chloride into water, heat to 100°C, and stir for 24 minutes;
[0069] 2) adding rubidium hydroxide to the system of step 1), keeping the temperature for reaction for 4 hours, and then adding phosphorous acid to continue the reaction for 0.5 hours;
[0070] 3) adding melamine to the system of step 2), stirring for 30 minutes, adding cyanuric acid and keeping the temperature for 0.5 hours, and obtaining flame-retardant modified hypophosphite after post-treatment;
[0071] In steps 1) to 3), m(magnesium hypophosphite):m(magnesium chloride+rubidium hydroxide+phosphorous acid):m(melamine+cyanuric acid):m(water)=100:105:130:800, m(magnesium hypophosphite) represents the mass of magnesium hypophosphite, m(magnesium chloride+rubidium hydroxide+phosphorous acid) represents the total mass of magnesium chloride, rubidium hydroxide and phosphorous acid, m(melamine+cyanuric acid) represents the total mass of melamine and cyanuric acid, and m(water) represents the mass of water; the molar ratio of magnesium chloride, rubidium hydroxide and phosphorous acid is 1:6:3; the molar ratio of melamine and cyanuric acid is 1:0.8.
[0072] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of magnesium hypophosphite, an inner layer of magnesium phosphite, and an outer layer of melamine cyanurate; the diameter of the inner core is 50 μm, the thickness of the inner layer is 150 μm, and the thickness of the outer layer is 37 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 380°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0073] Example 4
[0074] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0075] 1) Add barium hypophosphite and zinc nitrate into water, heat to 85°C, and stir for 20 minutes;
[0076] 2) adding cesium hydroxide to the system of step 1), keeping the temperature for reaction for 0.5 h, and then adding phosphorous acid to continue the reaction for 0.5 h;
[0077] 3) Melamine was added to the system of step 2), and after stirring for 20 minutes, cyanuric acid was added and the mixture was kept warm for 2 hours, and flame-retardant modified hypophosphite was obtained after post-treatment;
[0078] In steps 1) to 3), m(barium hypophosphite):m(zinc nitrate+cesium hydroxide+phosphorous acid):m(melamine+cyanuric acid):m(water)=100:100:100:500, m(barium hypophosphite) represents the mass of barium hypophosphite, m(zinc nitrate+cesium hydroxide+phosphorous acid) represents the total mass of zinc nitrate, cesium hydroxide and phosphorous acid, m(melamine+cyanuric acid) represents the total mass of melamine and cyanuric acid, and m(water) represents the mass of water; the molar ratio of zinc nitrate, cesium hydroxide and phosphorous acid is 1:1.5:3; the molar ratio of melamine and cyanuric acid is 1:1.2.
[0079] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of barium hypophosphite, an inner layer of zinc phosphite, and an outer layer of melem cyanurate; the diameter of the inner core is 10 μm, the thickness of the inner layer is 40 μm, and the thickness of the outer layer is 42 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 377°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0080] Example 5
[0081] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0082] 1) Add zinc hypophosphite and tin chloride into water, heat to 85°C, and stir for 15 minutes;
[0083] 2) adding strontium hydroxide to the system of step 1), keeping the temperature for reaction for 4 hours, and then adding phosphorous acid to continue the reaction for 1 hour;
[0084] 3) adding graphite-like carbon nitride to the system of step 2), stirring for 25 minutes, adding cyanuric acid and keeping the temperature for 3 hours, and obtaining flame-retardant modified hypophosphite after post-treatment;
[0085] In steps 1) to 3), m(zinc hypophosphite):m(tin chloride + strontium hydroxide + phosphorous acid):m(graphite-like carbon nitride + cyanuric acid):m(water)=100:50:200:1000, m(zinc hypophosphite) represents the mass of zinc hypophosphite, m(tin chloride + strontium hydroxide + phosphorous acid) represents the total mass of tin chloride, strontium hydroxide and phosphorous acid, m(graphite-like carbon nitride + cyanuric acid) represents the total mass of graphite-like carbon nitride and cyanuric acid, and m(water) represents the mass of water; the molar ratio of tin chloride, strontium hydroxide and phosphorous acid is 1:3:3; the molar ratio of graphite-like carbon nitride and cyanuric acid is 1:1.1.
[0086] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of zinc hypophosphite, an inner layer of tin phosphite, and an outer layer of cyanuric acid-based graphite carbon nitride; the diameter of the inner core is 22 μm, the thickness of the inner layer is 37 μm, and the thickness of the outer layer is 10 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 372°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0087] Example 6
[0088] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0089] 1) Add tin hypophosphite and stannous chloride into water, heat to 90°C, and stir for 20 minutes;
[0090] 2) adding barium hydroxide to the system of step 1), keeping the temperature for reaction for 2 hours, and then adding phosphorous acid to continue the reaction for 2 hours;
[0091] 3) adding melamine and dicyandiamide to the system of step 2), stirring for 15 minutes, adding cyanuric acid and keeping warm for 2.5 hours, and obtaining flame-retardant modified hypophosphite after post-treatment; wherein the mass ratio of melamine to dicyandiamide is 1:2;
[0092] In steps 1) to 3), m(tin hypophosphite):m(stannous chloride+barium hydroxide+phosphorous acid):m(melamine+dicyandiamide+cyanuric acid):m(water)=100:20:200:500, m(tin hypophosphite) represents the mass of tin hypophosphite, m(stannous chloride+barium hydroxide+phosphorous acid) represents the total mass of stannous chloride, barium hydroxide and phosphorous acid, m(melamine+dicyandiamide+cyanuric acid) represents the total mass of melamine, dicyandiamide and cyanuric acid, and m(water) represents the mass of water; the molar ratio of stannous chloride, barium hydroxide and phosphorous acid is 1:2:1.5; the molar ratio of melamine, dicyandiamide and cyanuric acid is 1:1.
[0093] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of tin hypophosphite, an inner layer of stannous phosphite, and an outer layer of melamine cyanurate and dicyandiamide cyanurate; the diameter of the inner core is 13 μm, the thickness of the inner layer is 62 μm, and the thickness of the outer layer is 44 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 365°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0094] Example 7
[0095] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0096] 1) Add stannous hypophosphite, ferric nitrate and barium chloride into water, heat to 85°C and stir for 25 minutes; wherein the mass ratio of ferric nitrate to barium chloride is 1:1;
[0097] 2) adding mercuric hydroxide to the system of step 1), keeping the temperature for reaction for 2 hours, and then adding phosphorous acid to continue the reaction for 1.5 hours;
[0098] 3) adding melamine and graphite-like carbon nitride to the system of step 2), stirring for 20 minutes, adding cyanuric acid and keeping warm for 1.5 hours, and obtaining flame-retardant modified hypophosphite after post-treatment; wherein the mass ratio of melamine to graphite-like carbon nitride is 1:1;
[0099] In steps 1) to 3), m(stannous hypophosphite):m(ferric nitrate+barium chloride+mercuric hydroxide+phosphorous acid):m(melamine+graphite-like carbon nitride+cyanuric acid):m(water)=100:50:150:1000, m(stannous hypophosphite) represents the mass of stannous hypophosphite, m(ferric nitrate+barium chloride+mercuric hydroxide+phosphorous acid) represents the total mass of ferric nitrate, barium chloride, mercuric hydroxide and phosphorous acid, m(melamine+graphite-like carbon nitride+cyanuric acid) represents the total mass of melamine, graphite-like carbon nitride and cyanuric acid, and m(water) represents the mass of water; the molar ratio of ferric nitrate to barium chloride, mercuric hydroxide and phosphorous acid is 1:5:1.5; the molar ratio of melamine to graphite-like carbon nitride and cyanuric acid is 1:0.9.
[0100] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of stannous hypophosphite, an inner layer of ferrous phosphite and barium phosphite, and an outer layer of melamine cyanurate and cyanuric acid-based graphite carbon nitride; the diameter of the inner core is 14 μm, the thickness of the inner layer is 81 μm, and the thickness of the outer layer is 32 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 362°C, and it is not a flammable solid as determined by the method in GB19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0101] Example 8
[0102] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0103] 1) Add cerium hypophosphite and ferrous chloride into water, heat to 90°C, and stir for 30 minutes;
[0104] 2) adding silver diammine hydroxide to the system of step 1), keeping the temperature for reaction for 2.5 hours, and then adding phosphorous acid to continue the reaction for 2 hours;
[0105] 3) adding melamine and melamine to the system of step 2), stirring for 20 minutes, adding cyanuric acid and keeping warm for 1.5 hours, and obtaining flame-retardant modified hypophosphite after post-treatment; wherein the mass ratio of melamine to melamine is 2:1;
[0106] In steps 1) to 3), m(cerium hypophosphite):m(ferrous chloride+silver diammine hydroxide+phosphorous acid):m(melamine+melamine+cyanuric acid):m(water)=100:100:10:800, m(cerium hypophosphite) represents the mass of cerium hypophosphite, m(ferrous chloride+silver diammine hydroxide+phosphorous acid) represents the total mass of ferrous chloride, silver diammine hydroxide and phosphorous acid, m(melamine+melamine+cyanuric acid) represents the total mass of melamine, melem and cyanuric acid, and m(water) represents the mass of water; the molar ratio of ferrous chloride, silver diammine hydroxide and phosphorous acid is 1:4:2; the molar ratio of melamine to melem and cyanuric acid is 1:1.5.
[0107] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of cerium hypophosphite, an inner layer of ferrous phosphite, and an outer layer of melamine cyanurate and melamine cyanurate; the diameter of the inner core is 23 μm, the thickness of the inner layer is 94 μm, and the thickness of the outer layer is 27 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 361°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
[0108] Example 9
[0109] A method for preparing a flame retardant modified hypophosphite, comprising the following steps:
[0110] 1) adding cerium hypophosphite, tin hypophosphite and lanthanum chloride into water, heating to 95°C and stirring for 30 minutes; wherein the mass ratio of cerium hypophosphite to tin hypophosphite is 1:1;
[0111] 2) adding calcium hydroxide and ammonia water to the system of step 1), keeping the temperature for reaction for 3 hours, and then adding phosphorous acid to continue the reaction for 4 hours; wherein the mass ratio of calcium hydroxide to ammonia water is 1:3;
[0112] 3) adding melamine, melamine and melamine to the system of step 2), stirring for 30 minutes, adding cyanuric acid and keeping warm for 2 hours, and obtaining flame-retardant modified hypophosphite after post-treatment; wherein the mass ratio of melamine, melamine and melamine is 1:1:1;
[0113] In steps 1) to 3), m(cerium hypophosphite + tin hypophosphite): m(lanthanum chloride + calcium hydroxide + ammonia water + phosphorous acid): m(melamine + melamine + melem + cyanuric acid): m(water) = 100:20:10:1000, m(cerium hypophosphite + tin hypophosphite) represents the mass of cerium hypophosphite and tin hypophosphite, m(lanthanum chloride + calcium hydroxide + ammonia water + phosphorous acid) represents the total mass of lanthanum chloride, calcium hydroxide, ammonia water and phosphorous acid, m(melamine + melamine + melem + cyanuric acid) represents the total mass of melamine, melamine, melem and cyanuric acid, and m(water) represents the mass of water; the molar ratio of lanthanum chloride, calcium hydroxide, ammonia water and phosphorous acid is 1:3:2; the molar ratio of melamine, melamine, melem and cyanuric acid is 1:1.2.
[0114] The flame retardant modified hypophosphite finally obtained has a double-layer coating structure, with an inner core of cerium hypophosphite and tin hypophosphite, an inner layer of lanthanum phosphite, and an outer layer of melamine cyanurate, melene cyanurate and melem cyanurate; the diameter of the inner core is 34 μm, the thickness of the inner layer is 135 μm, and the thickness of the outer layer is 28 μm; the 1wt% thermal decomposition temperature of the flame retardant modified hypophosphite is 355°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specifications for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
Claims
1. A flame retardant modified hypophosphite, characterized in that: It has a double-layer coating structure, with the inner core being hypophosphite, the inner layer being phosphite, and the outer layer being cyanurate.
2. A flame retardant modified hypophosphite according to claim 1, characterized in that: The diameter of the inner core is 1 to 50 μm, the thickness of the inner layer is 10 to 150 μm, and the thickness of the outer layer is 10 to 50 μm.
3. A flame retardant modified hypophosphite according to claim 1, characterized in that: The hypophosphite is one or more of aluminum hypophosphite, calcium hypophosphite, magnesium hypophosphite, zinc hypophosphite, tin hypophosphite, stannous hypophosphite, cerium hypophosphite and barium hypophosphite.
4. The flame retardant modified hypophosphite according to claim 1, characterized in that: The phosphite is one or more of calcium phosphite, aluminum phosphite, magnesium phosphite, zinc phosphite, tin phosphite, stannous phosphite, iron phosphite, lanthanum phosphite and barium phosphite.
5. The flame retardant modified hypophosphite according to claim 1, characterized in that: The cyanurate is one or more of melamine cyanurate, dicyandiamide cyanurate, melamine cyanurate, melem cyanurate and cyanuric acid-based graphite carbon nitride.
6. The flame retardant modified hypophosphite according to claim 1, characterized in that: The 1wt% thermal decomposition temperature of the flame-retardant modified hypophosphite is ≥350°C, and it is not a flammable solid as determined by the method in GB 19521.1 "Safety Specification for Inspection of Hazardous Characteristics of Flammable Solid Dangerous Goods".
7. A method for preparing a flame retardant modified hypophosphite as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Add hypophosphite and soluble metal salt into water, heat to 80-100°C, and stir for 15-30 minutes; 2) adding alkaline substance I to the system of step 1), keeping the temperature for reaction for 0.5 to 4 hours, and then adding phosphorous acid to continue the reaction for 0.5 to 4 hours; 3) Add alkaline substance II to the system of step 2), stir for 15 to 30 minutes, add cyanuric acid and keep warm for 0.5 to 4 hours, and obtain flame-retardant modified hypophosphite after post-treatment.
8. The method according to claim 7, characterized in that m(hypophosphite):m(soluble metal salt+alkaline substance I+phosphorous acid):m(alkaline substance II+cyanuric acid):m(water)=100:10~200:10~200:500~1000, m(hypophosphite) represents the mass of hypophosphite, m(soluble metal salt+alkaline substance I+phosphorous acid) represents the total mass of soluble metal salt, alkaline substance I and phosphorous acid, m(alkaline substance II+cyanuric acid) represents the total mass of alkaline substance II and cyanuric acid, m(water) represents the mass of water; the molar ratio of soluble metal salt, alkaline substance I and phosphorous acid is 1:1~6:1~3; the molar ratio of alkaline substance II and cyanuric acid is 1:0.8~1.
5.
9. The method according to claim 7, characterized in that: The soluble metal salt is one or more of soluble calcium salt, aluminum salt, magnesium salt, zinc salt, tin salt, stannous salt, iron salt, ferrous salt, lanthanum salt and barium salt; the alkaline substance I is one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, strontium hydroxide, barium hydroxide, mercuric hydroxide, diammine silver hydroxide, calcium hydroxide and ammonia water; the alkaline substance II is one or more of melamine, dicyandiamide, melamine, melamine and graphite-like carbon nitride.
Citation Information
Patent Citations
Preparation method of microcapsule aluminum hypophosphite flame retardant
CN105457574A